Analysis of Student Entrepreneurial Interest Stimulators at Universities in Pematangsiantar City - Lenny Dermawan Sembiring; Hery Pandapotan Silitonga; Christine Loist; Onita Sari Sinaga; Acai Sudirman (Valid: Jurnal Ilmiah, 2022)
In Indonesia, the development of small and micro enterprises has increased significantly every year. This informs that the interest in entrepreneurship in Indonesia is very high. In the future, it is expected to become one of the pioneers of stimulus for economic progress in developed countries. The main purpose of this study was to analyze and examine the effect of entrepreneurship knowledge, self-efficacy, and social media utilization on student entrepreneurial interest in universities in Pematangsiantar City. This study's research method includes library and field research design with a quantitative approach. The research subjects taken in this study were SME actors in the culinary sector in Pematangsiantar City. Data collection techniques using observation, interviews, questionnaires, and documentation. The data analysis method used is Partial Least Square (PLS). The study stated positive and significant results between entrepreneurship knowledge, self-efficacy, and social media utilization with entrepreneurial interest. The implications of this study conclude in the digital age when in this case, substantial knowledge from students about entrepreneurship is needed to turn ideas into businesses in order to be able to realize their visions into reality.